Irrigation of Young Cork Oaks under Field Conditions—Testing the Best Water Volume - Camilo-Alves, Constança (2020)
This study is the beginning of the first long-term study on cork oak irrigation under field conditions, with a structural-functional approach. Cork oaks are currently facing disturbances affecting cork quality and quantity, jeopardizing the future of the economic sector. There is a need for new production techniques that maximize cork oak growth and vitality. In this study, irrigation was implemented in a new intensive cork oak plantations to test the best irrigation volume. The long-term goal is to improve tree growth with minimum water requirements. A 6 ha intensive plantation was installed in Coruche, Portugal. The experimental plot consisted of a subsurface drip fertigation system, buried 40 cm deep; with five independent irrigation treatments. It was tested four irrigation volumes during the dry period—21 weeks in the summer of 2016—ranging from 1.88 mm to 5.62 mm a week. Information on meteorological conditions, soil moisture profile and leaf stomatal conductance were gathered periodically and dendrometric measurements were performed before and after the treatments. Cork oaks’ structural and functional parameters were associated with irrigation volume Response to irrigation showed an inflection point in treatment 2, corresponding to a water supply of 3.12 mm per week: below the inflection point, stomatal conductance was reduced by 15% and relative diameter growth at the base was reduced by 10%. Stomatal conductance also showed a positive relationship with soil moisture below the irrigation tubes and with plants’ stem diameter. In conclusion, irrigation supply during the period of water stress improved function and structure of cork oaks seedlings under field conditions. These results suggest that irrigation can be a viable alternative to improve cork oak growth in afforestation and reforestation